A Common Founder Mutation in the EDA-A1 Gene in X-Linked Hypodontia - Kurban, Mazen (S. Karger AG, 2010)
BACKGROUND: X-linked recessive hypohidrotic ectodermal dysplasia (XLHED; OMIM 305100) is a rare genodermatosis characterized clinically by developmental abnormalities affecting the teeth, hair and sweat glands. Mutations in the EDA-A1 gene have been associated with XLHED. Recently, mutations in the EDA-A1 gene have also been implicated in isolated X-linked recessive hypodontia (XLRH; OMIM 313500). METHODS: We analyzed the DNA from members of 3 unrelated Pakistani families with XLRH for mutations in the EDA-A1 gene through direct sequencing and performed haplotype analysis. RESULTS: We identified a common missense mutation in both families designated c.1091T→C (p.M364T). Haplotype analysis revealed that this is a founder mutation in the 3 families. CONCLUSION: XLHED is a syndrome with variable clinical presentations that contain a spectrum of findings, including hypodontia. We suggest that XLRH should be grouped under XLHED as both share several phenotypic and genotypic similarities.